PEMBENTUKAN TEORI SOSIOLOGI POLITIK OLEH IBNU KHALDUN - Agustina Damanik (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
This paper will try to illustrate the concepts offered by Ibn Khaldun on State and government, with the main explanations regarding the concept  of  ashabiyah  (group solidarity) and its role on state formation, rise and collapse.  According to  theIbnu Khaldun, ashabiyyah is the driving force of the country  and  the  foundation for the establishment of a state or dynasty . Ashabiyyah have a major role in the expansion of the country after the establishment of the country's foundation. When ashabiyyah is strong , the states can be expanded otherwise if asabiyyah weak , then the area of the states appears relativelylimited